The INSL3-LGR8/GREAT Ligand-Receptor Pair in Human Cryptorchidism - Ferlin, Alberto; Simonato, Mauro; Bartoloni, Lucia; Rizzo, Giorgia; Bettella, Andrea; Dottorini, Tania; Dallapiccola, Bruno; Foresta, Carlo (The journal of clinical endocrinology and metabolism, 2003)
Testicular descent is a complex multistep embryonic process requiring the interaction between anatomical and hormonal factors. Failure in any of these steps results in cryptorchidism, the most frequent congenital anomaly of the urogenital tract in human males. Evidence for a genetic cause for cryptorchidism is numerous and supported by animal models. In particular, INSL3 and LGR8/GREAT proteins seem to act as ligand and receptor, respectively, and to have a role in gubernaculum development involved in testicular descent. In a cohort of 87 ex-cryptorchid patients and 80 controls, we looked for mutations in INSL3 and LGR8/GREAT genes by sequencing. Patients were classified on the basis of seminal, hormonal, and testicular cytological analyses. We found three mutations in the INSL3 gene in four patients and one LGR8/GREAT mutation in four patients (8 of 87, 9.2%). The eight patients show different phenotypes, ranging from normozoospermia to complete azoospermia, and from bilateral cryptorchidism to retractile testes. Furthermore, the endocrine function of the testis appears normal in all subjects. The findings of our study demonstrate that INSL3-LGR8/GREAT mutations are frequently associated with human cryptorchidism and are maternally inherited. The only clinical consequence of alterations of the INSL3-LGR8/GREAT system seems to be failure of the testis to normally descend in the scrotum during embryonic development, without affecting the spermatogenic and endocrine components of the testis itself.